Overview of artemisinin effectiveness during outset years of its implementation in the western Brazilian Amazon - Pinto, Raquel de Medeiros; Sampaio, Vanderson de Souza; Melo, Gisely Cardoso de; Costa Alecrimm, Maria das Gracas; Mattoss, Karine; Perdomo, Renata Trentin; Cordeiro, Sabrine da Costa; Alves Parente, Ana Flavia; Carvalho, Lidia Raquel de [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Guimaraes Lacerda, Marcus Vinicius; Monteiro, Wuelton Marcelo; et al. (Fundaco Oswaldo Cruz, 2019)
BACKGROUND The elimination of malaria depends on the blocking of transmission and of an effective treatment. In Brazil, artemisinin therapy was introduced in 1991, and here we present a performance overview during implementation outset years. METHODS It is a retrospective cohort (1991 to 2002) of patients treated in a tertiary centre of Manaus, with positive microscopic diagnosis of Plasmodium falciparum malaria, under treatment with using injectable or rectal artemisinin derivatives, and followed over 35-days to evaluate parasite clearance, death and recurrence. FINDINGS This cohort outcome resulted 97.6% (1554/1593) of patients who completed the 35-day follow-up, 0.6% (10/1593) of death and 1.8% (29/1593) of follow-up loss. All patients that died and those that presented parasitaemia recurrence had pure P. falciparum infections and received monotherapy. Considering patients who completed 35-day treatment, 98.2% (1527/1554) presented asexual parasitaemia clearance until D4 and 1.8% (27/1554) between D5-D10. It is important to highlight that had no correlation between the five treatment schemes and the sexual parasite clearance. Finally, it is noteworthy that we were able to observe also gametocytes carriage during all follow-up (D0-D35). MAIN CONCLUSIONS Artemisinin derivatives remained effective in the treatment of falciparum malaria during first 12-years of use in north area of Brazil.
Keywords: Plasmodium falciparum; artemisinin; parasite clearance; drug resistance; treatment effectiveness; cohort study